Proses Sandblasting Dalam Proses Fabrikasi Baja Struktur Pada Proyek Refinery Development Master Plan (RDMP) di PT AJP - Hasbi Risqullah; Kardiman Kardiman; Iman Dirja (Peneliti.net, 2022)
Manufacturing industry is a process that is part of a branch of industry that uses a number of modern equipment such as industrial machines, regular and measurable management programs to transform raw goods into finished and marketable goods. One of the processes in the manufacturing industry is fabrication. This fabrication process goes through various stages until it becomes a ready-to-use product. The fabrication process has several stages, including marking, cutting, drilling, assembling, welding, checking, finishing, sandblasting, and painting. Sandblasting is one of the stages of the fabrication process. This process performs metalworking where the metal surface is made to be rough and flat with a certain degree of roughness and a certain erosion rate, by firing an abrasive material to the metal surface with a certain pressure. This process is carried out with the aim that the metal surface becomes rough, so that paint or other coating materials can stick to the metal surface well, not easily peeled off, and avoid corrosion. This process also goes through several stages of checking or inspection referring to predetermined standards so that in the next stage there are no obstacles.